PERAN DOSEN AMNUS BANJARMASIN DALAM MENGOPTIMALKAN PEMUDA MENUJU KAMPUNG MANDIRI DALAM PROGRAM BEDAH RUMAH DICEMPAKA SARI KOTA BANJARMASIN TAHUN 2022 BANJARMASIN - Rusdi Bahar; Wildani Khotami (Balanting, 2022)
AbstractThe purpose of this community service activity is to try to help in increasing the ability to recognize potential that can beused to solve their own problems, it can be in the form of the ability to recognize problems, causes and ways to solve themthrough deliberation groups with residents without having to create dependence on the roles performed. by the communityservice team. Through these groups, a bond of togetherness will grow, the courage to express opinions from all members ofthe community. So that the decision-making process becomes a shared property so that good communication is establishedand synergized in building prosperity around.Keywords: social, culture